Analyzing rice production and consumption using a system dynamics model in East Kalimantan: Analisis produksi dan konsumsi beras menggunakan model sistem dinamik di Kalimantan Timur - Cahyono, Tri Wahyu; Tokuda, Hiromi; Amrullah, Eka Rastiyanto; Laya, Willie Samodra (Analisis Kebijakan Pertanian, 2025)
The decision to relocate the capital of Indonesia from Jakarta to Ibu Kota Nusantara (IKN), in East Kalimantan poses significant challenges to food security, particularly concerning maintaining a balance between rice production and consumption. This study aims to predict the balance between rice demand and supply in the IKN area until 2030. This study uses a dynamic systems approach to estimate the impact of the IKN relocation on the dynamics of rice consumption and supply. By analyzing projected population migration and economic factors, this study estimates an increase in rice demand due to the influx of people to East Kalimantan. The study suggests several strategies to address this increase in rice demand, including optimizing agricultural land use for rice farming, promoting household income increases, and implementing price stabilization policies. With appropriate measures as suggested in this analysis, East Kalimantan can substantially reduce its dependence on rice supply from other regions and improve sustainable food security. This study emphasizes the importance of collaborative efforts with other rice-producing regions on the island of Kalimantan and rice production centers in Indonesia to strengthen food security in East Kalimantan.